2009
DOI: 10.1111/j.1468-2850.2009.01170.x
|View full text |Cite
|
Sign up to set email alerts
|

Current directions in videoconferencing tele-mental health research.

Abstract: The provision of mental health services via videoconferencing tele-mental health has become an increasingly routine component of mental health service delivery throughout the world. Emphasizing the research literature since 2003, we examine: 1) the extent to which the field of tele-mental health has advanced the research agenda previously suggested; and 2) implications for tele-mental health care delivery for special clinical populations. Previous findings have demonstrated that tele-mental health services are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
270
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(283 citation statements)
references
References 144 publications
(267 reference statements)
5
270
1
7
Order By: Relevance
“…I conducted all interviews through the videoconferencing software (e.g., Skype, Google Hangout, and Face Time). Recent literature supported the use of videoconferencing software by researchers when conducting interviews, and the similarities of these interviews to in-person interviews have been noted (Beck, 2005;Dicicco-Bloom & Crabtree, 2006;Richardson, Frueh, Grubaugh, Egede, & Elhai, 2009;Sedgwick & Spiers, 2009;Winzenburg, 2012). I maintained confidentiality by conducting interviews in a private room where only I was privy to participants' responses.…”
Section: Overview Of Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…I conducted all interviews through the videoconferencing software (e.g., Skype, Google Hangout, and Face Time). Recent literature supported the use of videoconferencing software by researchers when conducting interviews, and the similarities of these interviews to in-person interviews have been noted (Beck, 2005;Dicicco-Bloom & Crabtree, 2006;Richardson, Frueh, Grubaugh, Egede, & Elhai, 2009;Sedgwick & Spiers, 2009;Winzenburg, 2012). I maintained confidentiality by conducting interviews in a private room where only I was privy to participants' responses.…”
Section: Overview Of Methodologymentioning
confidence: 99%
“…Considering the evidence in the literature regarding videoconferencing as a valid means for conducting qualitative interviews, I believe videoconferencing was a costeffective and appropriate medium to use for my data collection. Richardson et al (2009) discussed the pertinent ethical and legal issues involved with videoconferencing. They suggested that researchers utilizing videoconferencing consider the issue of informed consent, especially with respect to recording the videoconference.…”
Section: Internet As a Data Collection Mediummentioning
confidence: 99%
“…More recently, Richardson and colleagues examined the body of literature on telemental health and also concluded that the treatment of many mental health conditions through telehealth can achieve clinical outcomes comparable to those achieved when the same treatments are provided face-to-face (Richardson, Frueh, Grubaugh, Egede, & Elhai, 2009). Their conclusion was drawn in part from the largest randomized and controlled telemental health trial (O'Reilly et al, 2007).…”
Section: Background Evidence Of Impact Of Telehealth On Health Outcomesmentioning
confidence: 99%
“…[16][17][18] Telepsychiatry has been proven to be reliable and acceptable to both patients and providers for non-urgent care and has great potential for emergency care. [19][20][21][22][23][24] The initial evaluation of the MHEC-RAP during the establishment phase concluded that the program was helpful for both providers and patients. 25,26 The present study is part of a further evaluation and was designed to document longer-term changes in service use, identify gaps in services use and inform further service development.…”
Section: Introductionmentioning
confidence: 99%